Cardiac metabolic imaging using hyperpolarized [1‐13C]lactate as a substrate. (8th May 2021) - Lau, Angus Z.; Chen, Albert P.; Cunningham, Charles H.
Abstract : Hyperpolarized (HP) [1‐ 13 C]lactate is an attractive alternative to [1‐ 13 C]pyruvate as a substrate to investigate cardiac metabolism in vivo: it can be administered safely at a higher dose and can be polarized to a degree similar to pyruvate via dynamic nuclear polarization. While 13 C cardiac experiments using HP lactate have been performed in small animal models, they have not been demonstrated in large animal models or humans. Utilizing the same hardware and data acquisition methods as the first human HP 13 C cardiac study, 13 C metabolic images were acquired following injections of HP [1‐ 13 C]lactate in porcine hearts. Data were also acquired using HP [1‐ 13 C]pyruvate for comparison. The 13 C bicarbonate signal was localized to the myocardium and had a similar appearance with both substrates for all animals. No 13 C pyruvate signal was detected in the experiments following injection of HP 13 C lactate. The signal‐to‐noise ratio (SNR) of injected lactate was 88 ± 4% of the SNR of injected pyruvate, and the SNR of bicarbonate in the experiments using lactate as the substrate was 52 ± 19% of the SNR in the experiments using pyruvate as the substrate. The lower SNR was likely due to the shorter T 1 of [1‐ 13 C]lactate as compared with [1‐ 13 C]pyruvate and the additional enzyme‐catalyzed metabolic conversion step before the 13 C nuclei from [1‐ 13 C]lactate were detected as 13 C bicarbonate. While challenges remain, the potential of HP lactate as a substrate for clinical metabolic imaging of human heart has been demonstrated. Abstract : Utilizing the same hardware and data acquisition methods as the first human HP 13 C cardiac study, 13 C metabolic images were acquired in porcine hearts following injections of HP [1‐ 13 C]lactate. Data were also acquired using HP [1‐ 13 C]pyruvate for comparison. The SNR of bicarbonate in the experiments using lactate as the substrate was 52 ± 19% of the SNR in the experiments using pyruvate as the substrate. While challenges remain, the potential of HP lactate as a substrate for clinical metabolic imaging of human heart has been demonstrated.